Fire protection provisions for pre-building codes shophouses repurposed into budget hotel: a Malaysian perspective - Dg Badariah Ag Ali; Farid Wajdi Akashah; Raha Sulaiman (Penerbit Universiti Kebangsaan Malaysia, 2018)
Fire can happen at any time in any situation that could risk the life safety of people and cause destruction to a property. Many countries around the world including Malaysia, have established and enforced fire protection provisions in their building codes to control the risk of building fire. Despite that, practising such provisions can be challenging to the pre-building codes buildings as they were built before it. Those buildings need to comply the current established provisions in ensuring it is safe from any fire hazards as a way to protect the occupants. Building occupants can be very vulnerable to fire at night time especially when they are in deep sleep. In the case of hotel buildings, the guests are usually unfamiliar with the building layout which could increase their risk to the fire hazards. A good understanding of fire protection provisions for buildings that are repurposed into hotels is a key factor in making sure that such building is safe for public use. Provisions on current building codes and regulations on both active and passive fire protection systems for pre-building codes buildings repurposed into hotels in Malaysia are critically discussed in this paper.